Microbiologic studies on mastitis in sheep - Mehmet ATEŞ; Osman ERGANİŞ; Osman KAYA; Mehmet ÇORLU (Eurasian Journal of Veterinary Sciences)
This investigation was performed on 800 milch sheep belonged two state farm in Konya region. Sheep were examined by elinical procedures and tested with California Mastitis test (CMT). Milk samples taken from sheep with maStitis (CMT scores, ++/+++) w ere cultured in aerobic, microaerophlic and anaerobic conditions for bacteriological and mycological examination bacteria isolated and identified were tested against Ampicillin, Streptomycin, Tetracyclin, Penicillin, Kanamycin, Erytromycin, Gentamyem and Chloramphenicol discs (Difco ). In this area, in the mammary glands of 13.5 % of the -tested sheep, mastitis was detected. Although the rates of elinical mastitis was 0.75 percent, subclinical mastitis in sheep was 12.75 percent. Microbiologic isolation were succeded from (75.0 %) 81 samples of 108 mastitic milk. But, there was mix infection in 8 samples. The percent values of isolated microorganisms were found as below : 57.3 % Staph. aureus, 9.0 % for E. coli, 7.9 %for Bacillus ssp. 5.0% for B. cereus, 5.0% for C. pyogenes (Actinomyces pyogenes), 3.4 % for Str. agalactiae, 3.4 % for C. pyogenes (Actinomyces pyogenes), 3.4% for Sir. agalactiae, 3.4% for K. pneumoniae, 3.4 %for Candida albicans, 2.2 % for B. subtilis, 1.1 %for Str. dysgalactiae and 1.1 for Enterobacter ssp. In antibiotic susceptibility tests, Staph. aureus isolates were found to be sensitive to Tetracyclin, Chloramphenicol and Erytromycin, at the rates of 76.0 %, 58.0 % and 38.0 %, respectively. E. coli strains were sensitive to Streptomycin (100 %) and Tetracyclin (100 %), C. pyogenes strains were sensitive at the rates of 100 %, 80.0% and 80.0 %, for Penicillin, Streptomycin and Chloramphenicol, respectively.